The possibilities of cultural tourism to construct peace: cease study in kataragama division, monaragala district, sri lanka - Shammika, D.L.A.H.; Silva, P.D.Y. (university of Jaffna, 2014)
This paper explores the potentials in cultural tourism in Sri Lanka to foster peace. The methodological approach taken to answer the research question was based on grounded theory. Kataragama and Detagamuwa Grama Sewaka Divisions (GSDs) within Kataragama Secretariat Division (SD) of Sri Lanka in Monaragala district have been the major historical sites to nurture the emerging theory of the study. In the hidden face of those sites the researcher has explored the potentials which could blur the margins of division between ethnic groups in Sri Lanka and channel the conscientization process to rediscover a common inheritance and identities. Main argument in this article is that the cultural tourism leads to inter cultural understanding, developing mutual relations and building trust among each other. Since the existing peace building approaches are more political, cultural tourism is a strategy could be developed in to practical achievement of the goals of peace building. Study suggests and predicts the implications for managing and designing cultural tourism in the aspects of peace.
Keywords: Conflict transformation; Ethnic groups; Grounded theory; Peace; Cultural tourism